Percepción de los cambios ambientales en los humedales de Oña-Saraguro - Briceño Salas, Johanna Paola (2014)
In recent years there has been a considerable increase of public participation as a key element in the design of public policies. One way to manage this is to investigate the perceptions that people have about the environment. This study aims to determine if people of the surrounding communities to the wetland complex Ona-Saraguro perceive or have perceived changes in their environment. As well as determine which demographic variables influence that perception; and if the changes mentioned were perceived as positive, negative, natural or anthropogenic. For this reason a semi-structured survey of 120 people with photo mosaics indicating the distribution of vegetation cover between the years of 1989 and 2008 was produced. The results of these photo-mosaics demonstrates that from 1989 to 2008 the native vegetation has diminished and has been replaced by cultivated areas and livestock, which coincides with the results of surveys regarding the perception of the people. Furthermore, these changes were seen as "bad", holding the humans responsible as actors of the changes